Low-oil-permeability, low-viscosity and high-thermal-conductivity two-component organic silica gel and preparation method thereof

By adopting low-permeability oil, low viscosity and high thermal conductivity two-component silicone gel, and using long-chain polyalkoxy silane treatment agent and multi-particle alumina filler, the existing thermal conductivity of low, high viscosity and high oil permeability are solved, achieving efficient thermal management and good construction performance.

CN119735954APending Publication Date: 2025-04-01SHEN ZHEN ZHENGJI IND CO LTD +1

Patent Information

Application Number
CN202411737454.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing thermally conductive silicone gels have problems such as low thermal conductivity, high viscosity, and high oil permeability, which affect the service life and construction performance of the product.

Method used

Low-permeability oil, low viscosity, high thermal conductivity, two-component silicone gel are used to reduce the viscosity and prevent free vinyl silicone oil from leaking out. At the same time, spherical alumina with different particle sizes is used as thermal filler to improve thermal conductivity.

Benefits of technology

The silicone gel has achieved low viscosity, low oil permeability and high thermal conductivity. The viscosity is between 290,000 and 520,000 mPa·s, the thermal conductivity is around 6.0 to 6.5W/(m·k), the oil permeability is less than 0.5%, and it is closely fitted with the substrate to reduce contact thermal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735954A_ABST
    Figure CN119735954A_ABST
Patent Text Reader

Abstract

The invention provides low-oil-permeability, low-viscosity and high-thermal-conductivity two-component organic silica gel and a preparation method thereof. The low-oil-permeability, low-viscosity and high-thermal-conductivity two-component organic silica gel is prepared from a component A and a component B according to the mass ratio of 1: 1. The component A is composed of vinyl silicone oil, hydrogen-containing silicone oil, a treating agent K, an inhibitor and a heat-conducting filler; and the component B is composed of vinyl silicone oil, a treating agent L, a catalyst, a pigment and a heat-conducting filler. The oil penetration rate of the two-component heat-conducting organic silicon gel prepared by the method is 0.39-0.60%, the viscosity is 290000-520000mPa. S, the heat conductivity coefficient is mainly distributed at about 6.0-6.5 W / (m * k), the hardness of the organic silicon gel is 47-60Shore 00, the bonding effect with a base material is good, the problems of easy volatilization, oil penetration and poor heat dissipation effect when the product is used in an electronic component can be effectively solved, and the application prospect is wide. Meanwhile, the viscosity is relatively low, and the construction performance of high-thermal-conductivity gel is considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of two-component thermally conductive silicone gel, and in particular to a two-component silicone gel with low oil permeability, low viscosity and high thermal conductivity and a preparation method thereof. Background Art

[0002] At present, electronic devices are developing towards miniaturization and high performance. The heat generated inside the equipment is becoming more and more concentrated. Effective thermal management technology is needed to ensure the stable operation of the equipment and extend its life. Two-component thermally conductive silicone gel has good weather resistance, electronic insulation, high and low temperature resistance, plasticity, thermal conductivity, and low oil permeability, which enables it to achieve excellent heat transfer effects in many complex working conditions and become an ideal choice for thermal management. However, the thermally conductive silicone gels currently on the market have the following problems: (1) Low thermal conductivity and poor heat dissipation effect, which cannot effectively and timely remove heat, affecting the service life of the product; (2) In order to improve the thermal conductivity, a large amount of thermally conductive fillers must be added to the formula, resulting in high viscosity of the glue and poor extrusion, affecting the construction performance; or adding metal powders and some expensive high thermal conductivity fillers to the formula, although the thermal conductivity is improved, the cost is greatly increased, and the electrical performance of the product is affected; (3) During long-term use, oil is easily precipitated and electronic components are contaminated, affecting use.

[0003] The Chinese patent document with publication number CN114437546A provides a method for preparing a high thermal conductivity silicone gel, which uses expensive materials such as metal powder, metal nitride, and metal carbide as thermal conductive fillers, which is costly and has a thermal conductivity of 4.5W / (m·k). The Chinese patent document with publication number CN117820866A provides a method for preparing a silicone thermal conductive gel, which uses silicone resin to coat alumina to improve the compatibility of powder and silicone oil to achieve the effect of reducing viscosity, wherein the thermal conductivity is 3.2W / (m·k) when the minimum viscosity is 790000mPa·s. The Chinese patent document with publication number CN118027413A provides an inorganic material surface treatment agent, preparation method, and application. Because the active functional group in its structure is a full alkoxy group, it cannot capture free vinyl groups. The thermal conductive silicone gel prepared with this surface treatment agent has a viscosity of 285000mPa·s, a thermal conductivity of 6.0W / (m·k), and an oil permeability of 0.58%. The Chinese patent document with publication number CN113248928A provides a thermally conductive silicone gel and its preparation method and application, wherein a long-chain alkyl group is introduced into the side group of a vinyl-containing organic polysiloxane, and under the steric effect of the long-chain alkyl group, the molar mass ratio of the hydrogen group in the hydrogen-containing organic polysiloxane and the vinyl group in the vinyl-containing organic polysiloxane is adjusted, and the thermally conductive filler is treated in advance, so that the prepared thermally conductive silicone gel is in a semi-fluid paste state, and the oil permeability is 0.63-0.85%. The Chinese patent document with publication number CN115895277A provides a pre-cured single-component thermally conductive gel and its preparation method, wherein the modified thermally conductive powder is prepared by modifying the thermally conductive powder with a modifier, the modifier is composed of a long-chain alkyl silane and a vinyl silane, and the thermal conductivity is only 3.4-3.5 W / (m·k). Chinese patent document with publication number CN117186847A provides a thermally conductive gel with low oil permeability and high thermal conductivity and a preparation method. Vinyl-containing organic polysiloxane and hydrogen-containing organic polysiloxane with specific structures are selected to react so that all vinyl groups react to reduce the oil permeability. The thermal conductivity of the organic silicone gel is 5.3-5.4W / (m·k) and the oil permeability is 0.51-0.53%.

[0004] In addition to low viscosity and high thermal conductivity, thermally conductive gels also need to have very low hardness so that they can fit tightly with the substrate, reduce contact thermal resistance, and achieve better heat dissipation effects. The low hardness of thermally conductive gels is generally achieved by reducing the ratio of hydrogen to vinyl and reducing the reaction crosslinking density, which results in a large amount of unreacted free vinyl silicone oil in the thermally conductive gel. After curing, when subjected to external extrusion or after a period of high-temperature aging, the free vinyl silicone oil is prone to precipitation, contaminating components while affecting the state and performance of the thermally conductive gel. Therefore, reducing the content of free vinyl silicone oil in the system is the key to solving the problem of easy oil seepage and precipitation of silicone oil in thermally conductive gels, and it is also a problem that needs to be considered in the early stages of product design. Summary of the invention

[0005] In view of the industry problems of addition-type thermally conductive silicone gel, such as high viscosity, poor extrusion, easy oil permeation, and low thermal conductivity, the present invention aims to develop a low-viscosity, low-oil permeability, and high-thermal conductivity silicone gel to solve the above industry problems, and provide a preparation method thereof.

[0006] The first object of the present invention is to provide a two-component silicone gel with low oil permeability, low viscosity and high thermal conductivity. The silicone gel is a two-component silicone gel consisting of component A and component B.

[0007] Optionally, a low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel is made of the following raw materials, measured in parts by mass:

[0008] Component A

[0009]

[0010] Component B

[0011]

[0012] Optionally, component B contains a pigment, and 0.1 to 0.5 parts of the pigment are used for every 10 parts of vinyl silicone oil, that is, the raw materials of component B are measured by mass as follows:

[0013]

[0014]

[0015] Optionally, the viscosity of the vinyl silicone oil in components A and B is 50-200 mPa·s, preferably 50-100 mPa·s. In order to reduce the volatile matter, the volatile matter in the vinyl silicone oil is preferably less than 200 ppm.

[0016] Optionally, the thermally conductive fillers described in components A and B are compounded with alumina having a particle size of 0.1 to 120 μm; preferably, the particle size is 0.1 to 90 μm, and the alumina is spherical alumina. The thermally conductive filler is preferably compounded with spherical alumina of various particle sizes, for example, spherical alumina having a particle size greater than 50 μm, spherical alumina having a particle size of 5 to 50 μm, spherical alumina having a particle size greater than 1 μm and less than 5 μm, and spherical alumina having a particle size less than 1 μm.

[0017] Optionally, the hydrogen content of the hydrogen-containing silicone oil in component A is 0.1% to 0.36%, preferably 0.18% to 0.36%. In order to reduce the volatile matter, the volatile matter in the hydrogen-containing silicone oil is preferably less than 200 ppm.

[0018] Optionally, the treatment agent K in component A contains a Si-H bond, and the structural formula of the treatment agent K is as follows:

[0019]

[0020] The structural formula of R1 is: -OCH3 or -OCH2CH3; the structural formula of R2 is: -(CH2) n -Si(OCH3)3 or -(CH2) n -Si(OCH2CH3)3, wherein n is a natural number of 2 to 16, and optionally n is any natural number between 2 and 16, including but not limited to 2, 5, 8, 10, 12, 14, 16, etc. Within this range, the larger n is, the better the modification effect on the filler is, and the silicone gel has greater advantages in low viscosity, low oil permeability, and high thermal conductivity. Preferably, n is a natural number of 12 to 16. The terminal hydrogen of the treatment agent K can react with the free vinyl silicone oil in the silicone gel to prevent the free vinyl silicone oil from seeping out, thereby reducing the oil permeability; the methoxy or ethoxy group of the treatment agent K can be hydrolyzed, and therefore can react with the hydroxyl group on the filler, and the purpose of modifying the filler and preventing the vinyl silicone oil from seeping out is achieved by the coordination of the two reactive groups of the terminal hydrogen and the methoxy group.

[0021] Optionally, the preparation method of the treatment agent K comprises the following steps:

[0022] (1) Add 0.33-0.66 mol of additive S1 and 0.25 g of Custer platinum catalyst with a platinum concentration of 3000 ppm into a three-necked flask and stir evenly;

[0023] (2) adding 0.3-0.6 mol of auxiliary agent S2 dropwise; stirring and reacting at room temperature for 30-120 min in a nitrogen atmosphere;

[0024] (3) removing unreacted raw materials by distillation under reduced pressure at 50° C.;

[0025] (4) Add activated carbon, stir and adsorb, let stand for 24 hours, filter and remove the residual platinum catalyst, and obtain powder treatment agent K.

[0026] Optionally, the auxiliary agent S1 is dimethoxydihydrosilane or diethoxydihydrosilane, and the auxiliary agent S1 is preferably dimethoxydihydrosilane;

[0027] Optionally, the auxiliary agent S2 is CH2=CH-(CH2) m -Si(OCH3)3 or

[0028] CH2=CH-(CH2) m -Si(OCH2CH3)3, m is a natural number between 0 and 14, and optionally m is any natural number between 0 and 14, including but not limited to 0, 2, 5, 8, 10, 12, 14, etc.

[0029] Optionally, the inhibitor in component A is one or more of ethynyl cyclohexanol, methyl butynol, and tetramethyl tetravinyl cyclotetrasiloxane.

[0030] Optionally, the catalyst in component B is a Speier catalyst or a Custer catalyst.

[0031] Optionally, the treatment agent L in component B is at least one of octyl trimethoxysiloxane, dodecyl trimethoxysilane, and hexadecyl trimethoxysilane, which are conventional treatment agents in the art and do not have Si-H bonds. Because component B contains a catalyst, and treatment agent K can directly crosslink with the platinum catalyst, in order to prevent the crosslinking reaction of the internal components of component B before mixing components A and B, treatment agent K is not used in component B, but treatment agent L is used, and treatment agent L can stably coexist with other components in component B including the catalyst.

[0032] The second object of the present invention is to provide a method for preparing a two-component silicone gel with low oil permeability, low viscosity and high thermal conductivity, comprising the following steps:

[0033] Preparation of component A:

[0034] (1) Preheat the kneader, add vinyl silicone oil, treatment agent K, hydrogen-containing silicone oil, inhibitor, and part of the thermal conductive filler, and knead at normal pressure for at least 5 minutes;

[0035] (2) adding the remaining thermal conductive filler and kneading at normal pressure for at least 10 minutes;

[0036] (3) vacuum kneading for at least 2 hours to obtain component A;

[0037] Preparation of component B:

[0038] (1) Preheat the kneader, add vinyl silicone oil, treatment agent L, platinum catalyst, part of thermal conductive filler, and pigment, and knead at normal pressure for at least 5 minutes;

[0039] (2) adding the remaining thermal conductive filler and kneading at normal pressure for at least 10 minutes;

[0040] (3) Vacuum kneading for at least 2 hours to obtain component B.

[0041] In the process of preparing component A and component B, the thermal conductive filler is added to the kneader at least twice for kneading, which is conducive to evenly dispersing the thermal conductive filler in other materials and avoiding adding all the thermal conductive filler to the kneader at once to cause equipment jamming.

[0042] Furthermore, in the preparation method of the low-permeability, low-viscosity and high-thermal-conductivity two-component silicone gel, the stirring equipment can be a kneader, the preheating temperature of the kneader is 60 to 100°C, the vacuum pressure is set to be less than -0.08MPa, and the stirring speed is 33 to 37r / min; the first addition of the thermally conductive filler is 50% of the total mass of the filler, and adding the thermally conductive filler in batches can be more conducive to dispersion.

[0043] The treatment agent K used in the present invention is a long-chain polyalkoxysilane. The long-chain structure has a better powder coating effect and a more obvious viscosity reducing effect. It also has a high boiling point and is not easy to volatilize or precipitate in the system. In addition, after the polyalkoxy structure in the molecule reacts with the moisture on the surface of the powder, it can combine with the hydroxyl group on the surface of the powder to a greater extent, thereby reducing the moisture in the system while improving the treatment efficiency of the powder, further reducing the viscosity of the silicone gel, and improving the processing performance.

[0044] The active silicon-hydrogen bonds are retained in the treatment agent K. Under the action of the platinum catalyst, it can capture the unreacted vinyl silicone oil (free) in the system and make it firmly exist in the system, which not only reduces the oil permeability of the thermal conductive gel, but also avoids the problem of excessive hardness due to excessive cross-linking.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects:

[0046] The viscosity of the organic silicon gel prepared by the present invention is 290000-520000 mPa·s, so it has good construction performance.

[0047] The thermal conductivity of the organic silicon gel prepared by the present invention is mainly distributed in the range of about 6.0 to 6.5 W / (m*k), and has good thermal conductivity.

[0048] The hardness of the organic silicone gel prepared by the present invention is 47-60 Shore 00, which meets the hardness range required when the organic silicone gel is bonded to a substrate, so the bonding effect with the substrate is good and the thermal conductivity of the organic silicone gel can be fully exerted.

[0049] The oil permeability of the organic silicon gel prepared by the invention is between 0.39% and 0.60%, which significantly reduces the oil permeability of the organic silicon gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is the structural formula of treatment agent K1;

[0051] Figure 2 is the structural formula of treatment agent K2;

[0052] Figure 3 is the structural formula of treatment agent K3;

[0053] Figure 4 It is the structural formula of treatment agent K4. DETAILED DESCRIPTION

[0054] 1. Compounding of thermal conductive fillers

[0055] Thermal conductive filler 1: 100 parts of 90 μm spherical alumina, 100 parts of 10 μm spherical alumina, 8 parts of 2 μm spherical alumina, 2 parts of 0.1 μm spherical alumina;

[0056] Thermal conductive filler 2: 100 parts of 70 μm spherical alumina, 100 parts of 10 μm spherical alumina, 8 parts of 2 μm spherical alumina, 2 parts of 0.1 μm spherical alumina;

[0057] Thermal conductive filler 3: 120 parts of 90 μm spherical alumina, 80 parts of 10 μm spherical alumina, 8 parts of 2 μm spherical alumina, and 2 parts of 0.1 μm spherical alumina.

[0058] Synthesis of Treatment Agent K

[0059] Synthesis of treatment agent K1:

[0060] Add 0.35 mol of dimethoxydihydrosilane and 0.25 g of Custer platinum catalyst with a platinum concentration of 3000 ppm into a three-necked flask and stir evenly;

[0061] 0.3 mol of vinyltrimethoxysilane was added dropwise; the reaction was stirred at room temperature in a nitrogen atmosphere for 40 min;

[0062] Unreacted raw materials were removed by distillation under reduced pressure at 50°C;

[0063] Activated carbon was added and stirred for adsorption, and the mixture was allowed to stand for 24 hours. The residual platinum catalyst was removed by filtration to obtain powder treatment agent K1.

[0064] Synthesis of treatment agent K2:

[0065] Add 0.35 mol of dimethoxydihydrosilane and 0.25 g of Custer platinum catalyst with a platinum concentration of 3000 ppm into a three-necked flask and stir evenly;

[0066] 0.3 mol of pentyltrimethoxysilane was added dropwise; the reaction was stirred at room temperature for 60 min under a nitrogen atmosphere;

[0067] Unreacted raw materials were removed by distillation under reduced pressure at 50°C;

[0068] Activated carbon was added and stirred for adsorption, and the mixture was allowed to stand for 24 hours. The residual platinum catalyst was removed by filtration to obtain powder treatment agent K2.

[0069] Synthesis of treatment agent K3:

[0070] Add 0.35 mol of dimethoxydihydrosilane and 0.25 g of Custer platinum catalyst with a platinum concentration of 3000 ppm into a three-necked flask and stir evenly;

[0071] 0.3 mol of n-dodecyltrimethoxysilane was added dropwise; the reaction was stirred at room temperature in a nitrogen atmosphere for 90 min;

[0072] Unreacted raw materials were removed by distillation under reduced pressure at 50°C;

[0073] Activated carbon was added and stirred for adsorption, and the mixture was allowed to stand for 24 hours. The residual platinum catalyst was removed by filtration to obtain powder treatment agent K3.

[0074] Treatment agent K4:

[0075] Add 0.35 mol of dimethoxydihydrosilane and 0.25 g of Custer platinum catalyst with a platinum concentration of 3000 ppm into a three-necked flask and stir evenly;

[0076] 0.3 mol of n-hexadecene trimethoxysilane was added dropwise; the reaction was stirred at room temperature for 120 min in a nitrogen atmosphere;

[0077] Unreacted raw materials were removed by distillation under reduced pressure at 50°C;

[0078] Activated carbon was added and stirred for adsorption, and the mixture was allowed to stand for 24 hours. The residual platinum catalyst was removed by filtration to obtain powder treatment agent K4.

[0079] 2. A specific example of the preparation of a two-component silicone gel with low oil permeability, low viscosity and high thermal conductivity is as follows:

[0080] Preparation of component A: (1) preheat the kneader to 80°C, add 8 parts of vinyl silicone oil, 1 part of treatment agent K, 2 parts of hydrogenated silicone oil, 0.02 parts of ethynyl cyclohexanol, and 110 parts of thermal conductive filler, and knead at normal pressure for 5 minutes at a speed of 35±2 r / min; (2) add the remaining 110 parts of thermal conductive filler, knead at normal pressure for 10 minutes at a speed of 35±2 r / min, and scrape the edges; (3) evacuate and knead for 2 hours with a vacuum pressure less than -0.08 MPa to obtain component A.

[0081] Preparation of component B: (1) preheat the kneader to 80°C, add 10 parts of vinyl silicone oil, 0.5 parts of treatment agent L, 0.4 parts of Custer platinum catalyst, 110 parts of thermal conductive filler, and 0.1 parts of pigment, and knead at normal pressure for 5 minutes at a speed of 35±2r / min; (2) add the remaining 110 parts of thermal conductive filler, knead at normal pressure for 10 minutes at a speed of 35±2r / min, and scrape the edges; (3) evacuate and knead for 2 hours with a vacuum degree of less than -0.08MPa to obtain component B.

[0082] The comparative example is consistent with the above preparation process.

[0083] Table 1 Comparison of key raw materials in Examples and Comparative Examples

[0084]

[0085] Beneficial effect verification

[0086] The performance of the two-component thermally conductive gel of the present invention was tested by the following test:

[0087] Viscosity test

[0088] The components A and B obtained in the examples and comparative examples were mixed in a mass ratio of 1:1, and the viscosity of the mixed components was tested according to GB / T2794-2013.

[0089] Hardness test

[0090] The components A and B obtained in the examples and comparative examples were mixed at a mass ratio of 1:1, and the hardness of the mixed components was tested according to ASTM D2240.

[0091] Thermal conductivity test

[0092] The thermal conductivity of the samples prepared in the examples and comparative examples was tested using a Taiwan Ruiling LW-9389 interface material thermal resistance and thermal conductivity coefficient tester in accordance with ASTM D5470.

[0093] Oil penetration test

[0094] Use an electronic analytical balance to weigh the initial mass W1 of the thermal conductive gel sample before the test.

[0095] Attach three layers of filter paper or oil-absorbing paper to the top and bottom of the thermal conductive gel sample, clamp it with glass fiber cloth (total mass W2), filter paper (oil-absorbing paper) and molybdenum foil in turn, and then clamp it with a fixture. Test and record the total mass W3 of the sample and glass fiber cloth after baking;

[0096] Calculation formula: Oil permeability (oil permeability) = [1-(W3-W2) / W1*100%.

[0097] Table 2 Comparison of silicone gel properties between the examples and the comparative examples

[0098]

[0099] From the comparison of Examples 1 to 4, it can be seen that as the chain length of the treatment agent K increases, the viscosity of the silicone gel gradually decreases, the thermal conductivity mainly shows an upward trend, the oil permeability gradually decreases, and the hardness is below 50, which meets the industry's requirements for low hardness silicone gels. It can be seen that within a certain range, the longer the molecular chain of the treatment agent K, the better the modification effect.

[0100] The hydrogen-containing silicone oil used in Example 5 has a higher hydrogen content than that in Example 4, and is more fully cross-linked with the vinyl silicone oil, thereby reducing the free vinyl silicone oil in the thermally conductive silicone gel, thereby significantly reducing the oil permeability. However, excessive cross-linking causes the hardness of the thermally conductive silicone gel to increase, exceeding the acceptable hardness. The silicone gel with too high a hardness cannot fit tightly to the substrate. Although the thermally conductive silicone gel itself has a high thermal conductivity, the thermally conductive silicone gel still cannot fit tightly to the substrate, resulting in poor heat dissipation effect.

[0101] The vinyl silicone oil in Example 6 is lower than that in Example 3, indicating that the vinyl silicone oil used in Example 6 contains more vinyl. At the same time, Example 6 increases the hydrogen content of the hydrogenated silicone oil so that it reacts with the large amount of vinyl in the vinyl silicone oil. Nevertheless, in order to ensure acceptable hardness, the final silicone gel still contains more free vinyl silicone oil. Therefore, the oil permeability of the silicone gel is relatively high, reaching 0.6%.

[0102] The treatment agents used in the A components of Comparative Examples 1 and 3 are methyl silicone oil and propyl trimethoxy silane, respectively, which are conventional treatment agents available on the market. Methyl silicone oil does not contain reactive groups methoxy or ethoxy, so it cannot combine with the hydroxyl groups on the surface of the powder. Therefore, the viscosity and oil permeability of Comparative Example 1 are higher than those of Example 3 and Example 4. Although the viscosity of Comparative Example 3 is relatively lower than that of Comparative Example 1, the oil permeability is higher than that of Comparative Example 1. It can be seen that the treatment agent K used in the present invention has achieved better results in reducing the viscosity and oil permeability of the silicone gel compared with the two conventional treatment agents available on the market used in the A components of Comparative Examples 1 and 3. Comparative Example 2 uses hexadecyl trimethoxy silane as a treatment agent in both component A and component B, and it still has a relatively high viscosity and oil permeability.

[0103] Conclusion: 1. From the above results, it can be seen that the use of long-chain alkyl can better treat powders and reduce viscosity; 2. Compared with conventional silane coupling agents, polyalkoxy structures have better treatment effects on powders; 3. Compared with the prior art, the polyalkoxy hydrogen silane used in the present invention can effectively capture free vinyl silicone oil in the thermally conductive gel, reduce the oil permeability without increasing the hardness. The two-component thermally conductive silicone gel prepared by the present invention has an oil permeability of less than 0.5%, a viscosity of less than 400000 mPa·s, and a thermal conductivity of 6.5W / (m·k), which can effectively solve the problems of easy volatility, oil permeation, and poor heat dissipation when such products are used in electronic components. At the same time, the viscosity is low, taking into account the construction performance of high thermal conductivity gel.

[0104] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, it should be understood that those skilled in the art can design many other modifications and implementations, which will fall within the scope and spirit of the principles disclosed in the present application. More specifically, within the scope disclosed in the present application, multiple variations and improvements can be made to the components and / or layout of the subject combination layout. In addition to the variations and improvements made to the components and / or layout, other uses will also be apparent to those skilled in the art.

Claims

1. A low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel, characterized in that: Made from the following raw materials in parts by mass: Component A Component B 2. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 1, characterized in that: The treatment agent K described in component A contains Si-H bonds, and the structural formula of the treatment agent K is as follows: The structural formula of R1 is: -OCH3 or -OCH2CH3; the structural formula of R2 is: -(CH2) n -Si(OCH3)3 or -(CH2) n -Si(OCH2CH3)3, wherein n is a natural number ranging from 2 to 16.

3. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 2, characterized in that: The n is a natural number ranging from 12 to 16.

4. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 2, characterized in that: The structural formula of the treatment agent K is selected from any one of the following K1 to K4:

5. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to any one of claims 2 to 4, characterized in that: The viscosity of the vinyl silicone oil in component A and component B is 50 to 200 mPa·s.

6. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 5, characterized in that: The viscosity of the vinyl silicone oil in component A and component B is 50 to 100 mPa·s.

7. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 5, characterized in that: The hydrogen content of the hydrogen-containing silicone oil described in component A is 0.18% to 0.36%.

8. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 6 or 7, characterized in that: The catalyst described in component B is a Speier catalyst or a Custer catalyst; The treatment agent L in component B is at least one of octyl trimethoxysiloxane, dodecyl trimethoxysilane and hexadecyl trimethoxysilane; The inhibitor in component A is one or more of ethynyl cyclohexanol, methyl butynol, and tetramethyl tetravinyl cyclotetrasiloxane.

9. The low-penetration, low-viscosity, high-thermal-conductivity two-component silicone gel according to claim 1, characterized in that: The thermal conductive fillers described in components A and B are compounded with alumina with a particle size of 0.1 to 120 μm, and the alumina is spherical alumina.

10. The method for preparing the low-penetration, low-viscosity and high-thermal-conductivity two-component silicone gel according to any one of claims 1 to 9, characterized in that: The following steps are involved: Preparation of component A: (1) Preheat the kneading machine to 60-100°C, add vinyl silicone oil, treatment agent K, hydrogen-containing silicone oil, inhibitor, and part of the thermal conductive filler, and knead at normal pressure for at least 5 minutes; (2) adding the remaining thermal conductive filler and kneading at normal pressure for at least 10 minutes; (3) vacuum kneading for at least 2 hours, with the vacuum pressure set to less than -0.08 MPa and the stirring speed at 33 to 37 r / min, to obtain component A; Preparation of component B: (1) Preheat the kneader to 60-100°C, add vinyl silicone oil, treatment agent L, platinum catalyst, part of thermal conductive filler, and pigment, and knead at normal pressure for at least 5 minutes; (2) adding the remaining thermal conductive filler and kneading at normal pressure for at least 10 minutes; (3) Vacuum kneading for at least 2 hours, with the vacuum pressure set to less than -0.08 MPa and the stirring speed at 33 to 37 r / min, to obtain component B.

Citation Information

Patent Citations

  • Heat-conducting silica gel as well as preparation method and application thereof

    CN113248928A

  • High-thermal-conductivity organic silicon gel and preparation method thereof

    CN114437546A

  • Pre-cured single-component heat-conducting gel and preparation method thereof

    CN115895277A

  • Heat-conducting gel with low oil permeability and high heat conductivity and preparation method thereof

    CN117186847A

  • Organosilicone heat-conducting gel and preparation method thereof

    CN117820866A

Cited By

  • Diamond-based high-thermal-conductivity TIM heat-conducting gel and preparation method thereof

    CN122405004A